Use of an EHR-Integrated Point-of-Care Mobile Medical Photography Application in a Pediatric Emergency Department - Castillo, Richmond M. (Appl Clin Inform, 2019)
Background  Mobile applications allow health care providers to capture point-of-care medical photographs and transfer them to the electronic health record (EHR). It is unclear how providers use these photographs or how they affect clinical care. Objectives  We aimed to understand the content, purpose, and outcomes of point-of-care medical photography performed in the pediatric emergency department (ED) at large academic medical center. Methods  A retrospective chart review was conducted of patients <21 years of age who were seen in the ED and photographed between March 29, 2015 and July 1, 2017 using a secure smartphone application integrated with the EHR. Inter-rater agreement and reliability between the two reviewers was assessed for the first 50 charts, and any discrepancies in interpretation were resolved before proceeding with the remaining data abstraction. The documented rationale for photography, content of photographs, and outcomes were recorded. Results  We identified 619 clinical encounters involving photographs of 605 patients who were eligible for inclusion. Skin was photographed in 499 (81%). The most common finding was rash ( N  = 177; 29%). Photos were of acceptable quality, with 569 (94%) achieving a score between 4 and 5 out of 5. The primary use of photography was documentation ( N  = 334; 54%), though teleconsultation was noted in 38 (6%). Nearly one-third ( N  = 187; 30%) of patients were seen in the ED or outpatient clinic for any reason within 2 weeks, and in 25 (13%), clinical notes explicitly referenced the initial photograph(s). In 53 (9%) cases, patients were photographed at a clinical visit in the subsequent 2 weeks, suggesting that photography was used to track changes over time. Conclusion  Documentation of findings using mobile point-of-care photography allows for high-fidelity documentation and facilitates continuity of care.